ISPH–PBD: coupled simulation of incompressible fluids and deformable bodies - Abu Rumman, Nadine; Nair, Prapanch; Müller, Patric; Barthe, Loïc; Vanderhaeghe, David (Visual Computer, 2020)
We present an efficient and stable method for simulating the two-way coupling of incompressible fluids and deformable bodies. In our method, the fluid is represented by particles, and simulated using divergence-free incompressible smoothed-particle hydrodynamics (ISPH). The deformable bodies are represented by polygonal meshes, where the elastic deformations are simulated using a position-based dynamics scheme. Our technique enforces incompressibility on the fluid using divergence-free constraints on the velocity field, while it effectively simulates the physical features of deformable bodies. Most current ISPH methods are struggling with the issue of free-surface boundary conditions. We handle this problem by introducing a novel free-surface formulation, where our free-surface model obviates the need to identify the surface particles. For the interaction between the fluid and the deformable solids, we model the forces that both phases, fluid and solid, exert upon each other. We demonstrate that our approach effectively handles complex coupling scenarios between fluids and thin deformable shells or highly deformable solids, and produces plausible results.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Deformable bodies; Fluids; ISPH; PBD; Thin shells